Cytoplasmic Retention of CDC6 Induces Premature Senescence in Immortalized Cells and Suppresses Tumor Formation in Mice - Akihiro Ueda; Noriko Yoneda-Kato; Yuji Yamanaka; Ikuko Nakamae; Jun-ya Kato (Journal of Hematology and Oncology Research, 2016)
Senescence is a powerful mechanism that prevents the development of tumors in vivo; however, once tumors are formed, most are refractory to senescence in response to oncogenic stress. Therefore, a novel pathway leading to senescence is required. We herein demonstrated that the cell cycle regulator CDC6 translocated from the nucleus to the cytoplasm during senescence in a leptomycin B-resistant manner. In order to evaluate the translocation of CDC6, we utilized an estrogen receptor (ER) tag to retain CDC6 in the cytoplasm. ER-tagged CDC6 was exclusively cytoplasmic, inhibited cell proliferation, and induced senescence-associated (SA) b-galactosidase activity. Furthermore, ER-CDC6 inhibited the transformation of mouse fibroblasts by the active ras oncogene in vitro, and suppressed tumor formation in NOD-SCID mice. Thus, CDC6 may play a critical role in the regulation of senescence in the cytoplasm in order to counteract tumorigenesis.
Keywords: cell cycle